Neurological manifestations of patients with mild-to-moderate COVID-19 attending a public hospital in Lima, Peru - Carcamo Garcia, Marco H. (2021)
Objective To determine the prevalence and characteristics of the most common neurological manifestations in Peruvian patients with mild-to-moderate COVID-19. Methods We conducted a single-center prospective, cross-sectional study at an isolation center functioning as a public acute-care hospital during the COVID-19 pandemic in Lima, the capital city of Peru. This was a convenience sample of patients with acute COVID-19 infection and mild-to-moderate respiratory symptoms who presented for hospital admission between September 25 and November 25, 2020. We interviewed participants and collected demographic, medical history and clinical presentation data; all participants underwent a complete physical and neurological examination. Descriptive statistics and prevalence ratios (PR) with corresponding 95% confidence intervals and p-values were calculated to explore between-groups differences. Results Of 199 patients with mild-to-moderate COVID-19 enrolled in this study, 83% presented with at least one neurological symptom (mean symptom duration 8 +/− 6 days). The most common neurological symptoms were headache (72%), hypogeusia or ageusia (41%), hyposmia or anosmia (40%) and dizziness (34%). Only 2.5% of the cohort had an abnormal neurological examination. The majority (42%) had no prior comorbidities. Presence of at least 1 neurological symptom was independently associated with fever, dyspnea, cough, poor appetite, sore throat, chest tightness or diarrhea, but not with comorbid conditions. Conclusions This cross-sectional study found that headaches, and smell and taste dysfunction are common among patients presenting with mild-to-moderate acute COVID-19 in Lima, Peru. International longitudinal studies are needed to determine the long-term neurological sequelae of COVID-19 during the acute and post-infectious period.